(3TQM YQhV GHf GdSbGWs - (3Ydj Hf RdaG GdgeOGfis; (3GHf GdSbGW , CHh YHO Gddgs ((3eOjfI aGS s)
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf gPG cJGH hVYJg Ydi YQhV GdeYQha HGHf GdSbGW abdJ GdYQhV efbhd hGdYQhV hgh GdfGMjI s
(3BNQgG (B:s
(3hbO fU GdNdjd Ydi PcQ Pdc ai cJGHg GdYQhV Je hGdMeO ddg QH GdYGdejf s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdHdGZIs